2019
DOI: 10.1108/ijchm-03-2018-0193
|View full text |Cite
|
Sign up to set email alerts
|

Motivations of undertaking CSR initiatives by independent hotels: a holistic approach

Abstract: Purpose The purpose of this study is to explore how senior managers of independent hotels perceive the notion of corporate social responsibility (CSR) through a holistic analysis of motivations of undertaking both social and environmental initiatives. Design/methodology/approach This study conducts qualitative interviews with 22 Malaysian senior hotel managers together with ethnographic observations. Findings Emergent themes show that CSR is a dynamic concept involving complex struggles and trade-offs betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 66 publications
1
40
0
Order By: Relevance
“…Second, this study adds to the growing body of literature on sustainability and sustainability communication for hospitality services (Ali et al , 2019; Font et al , 2017; Tölkes, 2018, 2020). Although prior studies by Abaeian et al (2019) and Ponnapureddy et al (2020) demonstrated that travelers prefer hotels that undertake corporate social responsibility initiatives, this study extends this stream of literature by examining when and how sustainability communication is effective in persuading travelers to choose eco-friendly hotels when traveling. The study findings indicate that communicating sustainability initiatives and practices effectively is critical for hotels to influence travelers’ minds positively.…”
Section: Discussionmentioning
confidence: 84%
“…Second, this study adds to the growing body of literature on sustainability and sustainability communication for hospitality services (Ali et al , 2019; Font et al , 2017; Tölkes, 2018, 2020). Although prior studies by Abaeian et al (2019) and Ponnapureddy et al (2020) demonstrated that travelers prefer hotels that undertake corporate social responsibility initiatives, this study extends this stream of literature by examining when and how sustainability communication is effective in persuading travelers to choose eco-friendly hotels when traveling. The study findings indicate that communicating sustainability initiatives and practices effectively is critical for hotels to influence travelers’ minds positively.…”
Section: Discussionmentioning
confidence: 84%
“…Undoubtedly, corporate social responsibility (CSR) has recently garnered considerable attention in the hospitality industry (Gao et al , 2020; Nyahunzvi, 2013; Wu et al , 2017; Zhang, 2014). A large body of hospitality research demonstrates that practicing CSR not only benefits society but also boosts a brand’s revenue and cultivates customer loyalty (Abaeian et al , 2019; Choi and Seo, 2019; Martínez and Del Bosque, 2013; Nyahunzvi, 2013; Shafieizadeh and Tao, 2020). Importantly, customer participation plays a critical role in the success of hospitality CSR marketing, motivating hospitality organizations to develop various strategies and programs to engage consumers in their CSR efforts (Giebelhausen et al , 2017; Mattila and Hanks, 2013; Wu et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(1) the content of CSR (Carroll, 1999;Lindgreen and Swaen, 2010;McWilliams, 2015;Volgger and Huang, 2019); (2) how companies integrate or implement CSR practices with their existing processes (Abaeian et al, 2019;Avetisyan and Ferrary, 2013;Basu and Palazzo, 2008;Esbenshade, 2016;Iyer and Jarvis, 2019;Jones Christensen et al, 2014;Ko et al, 2019); (3) how CSR efforts impact firm performance (de Grosbois, 2016;Kang et al, 2016); and, finally; and (4) how and what companies disseminate or report related to their CSR efforts (Bons on and Bednárová, 2015;Marano et al, 2017;Michelon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%